De la nature historique des pratiques d’ingénierie - Antonio Dias de Figueiredo (Revue d'anthropologie des connaissances)
Revisiting the history of engineering since its first prehistoric traces and focusing more carefully on the last three millennia, the article constructs a four-dimensional typology of the disciplines that fed engineering throughout the epochs and cultures. It shows that these four dimensions are never totally integrated but also that the most brilliant and innovative engineers have been able to play on the four boards and associate them fruitfully. The reflection opens to a relational concept of the multidimensionality of engineering, where the links between the different dimensions may matter more than the individual dimensions or the accumulation of their contents. This way, the article expresses a message of hope about the future of engineering to which it claims to contribute to, showing that disintegration through detachment of different, diverse and complex components is not and unescapable even not problematic anymore as soon as we think of engineering as the art of holding this diversity together.